(untitled) - Hobsbawn, Eric (New York, 1975)
In this book, Eric Hobsbawm chronicles the events and trends that led to the triumph of private enterprise and its exponents in the years between 1848 and 1875. Along with Hobsbawm's other volumes, this book constitutes and intellectual key to the origins of the world in which we now live.
Keywords: History, modern,Economic history; 19th century,1750-1918